2018
DOI: 10.1681/asn.2018030238
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Cell Transcriptome Atlas of the Mouse Glomerulus

Abstract: Three different cell types constitute the glomerular filter: mesangial cells, endothelial cells, and podocytes. However, to what extent cellular heterogeneity exists within healthy glomerular cell populations remains unknown. We used nanodroplet-based highly parallel transcriptional profiling to characterize the cellular content of purified wild-type mouse glomeruli. Unsupervised clustering of nearly 13,000 single-cell transcriptomes identified the three known glomerular cell types. We provide a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
172
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(193 citation statements)
references
References 37 publications
16
172
1
Order By: Relevance
“…This dataset comprised 23,108 cells, including 11,851 cells from cold-and 11,257 cells from warm-dissociated kidneys (see Methods). These cells were then annotated using scMatch [29] by comparing their expression to reference gene expression profiles extracted from three previously published single-cell or single-nucleus RNA-seq studies of adult mouse kidneys [26,30,31]. The inferred identities were then used to calculate cell-type-specific gene expression signatures and further refine the annotations (see Methods and Supplementary Fig.…”
Section: Single-cell Sequencing Reveals Heterogeneous Stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…This dataset comprised 23,108 cells, including 11,851 cells from cold-and 11,257 cells from warm-dissociated kidneys (see Methods). These cells were then annotated using scMatch [29] by comparing their expression to reference gene expression profiles extracted from three previously published single-cell or single-nucleus RNA-seq studies of adult mouse kidneys [26,30,31]. The inferred identities were then used to calculate cell-type-specific gene expression signatures and further refine the annotations (see Methods and Supplementary Fig.…”
Section: Single-cell Sequencing Reveals Heterogeneous Stress Responsementioning
confidence: 99%
“…Reference dataset. To construct the reference dataset for scMatch [29], we obtained gene counts and cell types reported in three single-cell (or single-nuclei) adult mouse kidney studies [26,30,31]. Counts were normalised to cell library size and averaged within each cell type to derive reference vectors ( Supplementary Fig.…”
Section: Inferring Cell Identitymentioning
confidence: 99%
“…For example, female mice and humans are more resistant to ischemia or ER-stress-invoked renal injury (Hodeify, 2013;Park et al, 2004;Aufhauser et al, 2016). Single nucleus and single cell RNA-sequencing (scRNA-seq) have provided new insight into the cellular make-up of mammalian organ systems including the kidney (Wu et al, 2019;Habib et al, 2017;Macosko et al, 2015;Adam et al, 2017;Chen et al, 2017;Park et al, 2018;Karaiskos et al, 2018;Han et al,2018). However, kidney studies have been largely male-centered and lack insight into higher order organization of cell types critical to kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse glomeruli have just been analyzed by scRNAseq at a large scale with a total of 13,000 glomerular cells being sequenced, resulting in mouse glomerular singlecell transcriptome atlas [80]. In this work, the authors identified three subpopulations of podocytes as well as a subset of endothelial cells exhibiting proliferative property as shown by expression of proliferation marker genes.…”
Section: Current Studies In the Field Of Kidney Research That Used Scmentioning
confidence: 99%
“…This approach gave rise to more precise dissection of cell types or subtypes compared with scRNA-seq of whole kidney, as described in the work by Park et al [79]. Another example is the scRNA-seq of mouse glomeruli by Karaiskos et al [80]. They resolved three subpopulations of podocytes in contrast with Park et al's [79] work based on scRNA-seq of entire kidney.…”
Section: Perspectivesmentioning
confidence: 99%